A social identity analysis of technological innovation in an action sport: judging elite half-pipe snowboarding. Issue 2 (14th March 2016) - Harding, Jason; Lock, Daniel; Toohey, Kristine
ABSTRACT: Research question: We explore how facets of the group identity shared by elite half-pipe snowboarding (EHPS) constituents (i.e. judges, athletes, and coaches) shape attitudes towards a proposed technological innovation to the existing judging process. Research methods: Forty-nine EHPS constituents (coaches, athletes, and judges) completed an open-ended questionnaire and email protocol. The sample included participants from 19 countries in Asia-Pacific, Europe, and North America; all of which participated, coached, or judged in Fédération Internationale de Ski (FIS) or Olympic EHPS competitions. Results and discussion: Participants valued the freedom, individuality, and performance progression the current subjective judging protocol endorses. However, performance progression and changes to the half-pipe have created an increasingly difficult judging task. Participant attitudes towards the proposed innovation varied based on whether it was used to compute athlete final scores or to assist judges with their decision-making. Positive attitudes stemmed from the technological innovation providing support to judges, while retaining the flexibility of the existing performance assessment process. Negative attitudes emerged due to perceptions the innovation would inhibit athlete freedom, creativity, and individuality. Implications: Sport managers need to pay close attention to the identity shared by constituents prior to implementing innovation processes. Doing so provides a basis to apply new technological innovations in alignment with the values and beliefs of importance to constituents.